How has Mobile Phone Penetration Stimulated Financial Development in Africa? - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
In the first macroeconomic empirical assessment of the relationship between mobile phones and finance, this paper examines the correlations between mobile phone penetration and financial development using two conflicting definitions of the financial system in the financial development literature. With the traditional IFS (2008) definition, mobile phone penetration has a negative correlation with traditional financial intermediary dynamics of depth, activity and size. However, when a previously missing informal-financial sector component is integrated into the definition, mobile phone penetration has a positive correlation with informal financial development. Three implications result: there is a growing role of informal finance; mobile phone penetration may not be positively assessed at a macroeconomic level by traditional financial development indicators and; it is a wake-up call for scholarly research on informal financial development indicators which will oriented monetary policy.
Keywords: E00; G20; L96; O17; O33; 330; Banking; Mobile Phones; Shadow Economy; Financial Development; Africa